Targeted Nanoparticles with High Heating Efficiency for the Treatment of Endometriosis with Systemically Delivered Magnetic Hyperthermia. Issue 24 (17th April 2022) - Park, Youngrong; Demessie, Ananiya A.; Luo, Addie; Taratula, Olena R.; Moses, Abraham S.; Do, Peter; Campos, Leonardo; Jahangiri, Younes; Wyatt, Cory R.; Albarqi, Hassan A.; Farsad, Khashayar; Slayden, Ov D.; et al.
Abstract: Endometriosis is a devastating disease in which endometrial‐like tissue forms lesions outside the uterus. It causes infertility and severe pelvic pain in ≈176 million women worldwide, and there is currently no cure for this disease. Magnetic hyperthermia could potentially eliminate widespread endometriotic lesions but has not previously been considered for treatment because conventional magnetic nanoparticles have relatively low heating efficiency and can only provide ablation temperatures (>46 °C) following direct intralesional injection. This study is the first to describe nanoparticles that enable systemically delivered magnetic hyperthermia for endometriosis treatment. When subjected to an alternating magnetic field (AMF), these hexagonal iron‐oxide nanoparticles exhibit extraordinary heating efficiency that is 6.4× greater than their spherical counterparts. Modifying nanoparticles with a peptide targeted to vascular endothelial growth factor receptor 2 (VEGFR‐2) enhances their endometriosis specificity. Studies in mice bearing transplants of macaque endometriotic tissue reveal that, following intravenous injection at a low dose (3 mg per kg), these nanoparticles efficiently accumulate in endometriotic lesions, selectively elevate intralesional temperature above 50 °C upon exposure to external AMF, and completely eradicate them with a single treatment. These nanoparticles also demonstrate promising potential as magnetic resonance imaging (MRI) contrast agents for precise detection of endometriotic tissue before AMF application. Abstract : Endometriosis is a debilitating systemic disease in which tissue that resembles the uterine lining (the endometrium) forms vascularized lesions outside the uterus, often disseminating to distal sites. Novel endometriosis‐targeted hexagonal nanoparticles efficiently accumulate in these lesions following systemic administration, enabling improved detection with MRI. Upon exposure to an external alternating magnetic field, nanoparticles generate heat within lesions, completely eliminating them.